2021
DOI: 10.15252/emmm.202114108
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of West Nile virus vaccine through large replacement of 3′ UTR with internal poly(A)

Abstract: The genus Flavivirus comprises numerous emerging and reemerging arboviruses causing human illness. Vaccines are the best approach to prevent flavivirus diseases. But pathogen diversities are always one of the major hindrances for timely development of new vaccines when confronting unpredicted flavivirus outbreaks. We used West Nile virus (WNV) as a model to develop a new liveattenuated vaccine (LAV), WNV-poly(A), by replacing 5ʹ portion (corresponding to SL and DB domains in WNV) of 3ʹ-UTR with internal poly(A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…The structure of flavivirus 3’ UTR and the production of sfRNAs have been reported as one of important determinants of viral pathogenicity [ 9 , 11 ]. Our recent study identified that a WNV mutant carrying a replacement of SL and DB domains of 3′ UTR with internal poly(A) tract was highly attenuate [ 32 ]. Although DB-dup virus contained duplicated DB sequences, there was still a large fragment of SL domain missing from its genome.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of flavivirus 3’ UTR and the production of sfRNAs have been reported as one of important determinants of viral pathogenicity [ 9 , 11 ]. Our recent study identified that a WNV mutant carrying a replacement of SL and DB domains of 3′ UTR with internal poly(A) tract was highly attenuate [ 32 ]. Although DB-dup virus contained duplicated DB sequences, there was still a large fragment of SL domain missing from its genome.…”
Section: Resultsmentioning
confidence: 99%
“…The reverse genetics system is a powerful molecular tool for RNA virus research and vaccine development. Infectious clones of flaviviruses such as Zika virus (ZIKV) and West Nile virus (WNV) have been successfully constructed and rationally engineered for vaccine design [45,46]. As ISFVs can only infect arthropod vectors and not the vertebrate hosts, they represent identical viral vectors for vaccine development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 3 SL is the only structure in the 3 UTR that is absolutely needed for viral production. Keeping only the 3 SL and replacing all other parts of the 3 UTR with an appropriate length of poly (A) sequence in WNV RNA results in a highly attenuated but viable virus [28].…”
Section: The Roles Of Domain 3 and 2 In Denv Rna Replicationmentioning
confidence: 99%